Unexpected Fe‐enriched compounds observed in Mg–Ce alloy: An atomic‐scale STEM investigation. Issue 6 (2nd June 2016) - Zheng, Jingxu; Chen, Bin
Summary: This paper investigates into the unexpected nanosize Fe‐enriched particles with defects incorporated, using EDS under STEM mode and atomic‐resolution HAADF. The particle that locates between eutectic Mg12 Ce phase and α‐Mg phase is identified as CeFe2 Si2 compound. Two types of defects are incorporated: Type‐I defect is Ce‐Si in a simple cubic lattice; Type‐II defect is Ce in a FCC lattice. The interface between the defect‐free CeFe2 Si2 and the defects is fully coherent. In addition, another two Ce/Fe/Si‐enriched particles are observed, proving that the enrichment of Ce, Fe, and Si is not an accidental phenomenon. The observed formation of Ce/Fe/Si‐enriched particles provides a possible explanation for the improvement in corrosion resistance and the purification effect induced by addition of rare earth elements into alloys. In addition, the present study demonstrates an advanced application of Cs‐corrected HAADF by successfully directly imaging the dislocation and complex defects incorporated in the compound and by achieving a one‐angstrom resolution. SCANNING 38:783–791, 2016. © 2016 Wiley Periodicals, Inc.